Age and Gender Disparities in Adverse Events Following COVID-19 Vaccination: Real-World Evidence Based on Big Data for Risk Management - Xiong, Xiaomo; Yuan, Jing; Li, Minghui; Jiang, Bin; Lu, Z. Kevin (Frontiers in Medicine, 2021)
Background: Two coronavirus disease 2019 (COVID-19) vaccines have received emergency use authorizations in the U.S. However, the safety of these vaccines in the real-world remains unknown. Methods: We reviewed adverse events (AEs) following COVID-19 vaccination among adults in the Vaccine Adverse Event Reporting System (VAERS) from December 14, 2020, through January 22, 2021. We compared the top 10 AEs, serious AEs, as along with office and emergency room (ER) visits by age (18-64 years, ≥ 65 years) and gender (female, male). Results: There were age and gender disparities among adults with AEs following COVID-19 vaccination. Compared to younger adults aged between 18 and 64 years, older adults were more likely to report serious AEs, death, permanent disability, and hospitalization. Males were more likely to report serious AEs, death, and hospitalization compared to females. Conclusions: COVID-19 vaccines are generally safe but possible age and gender disparities in reported AEs may exist.